Analisis Penerapan Nilai – Nilai Profil Pelajar Pancasila Dalam Pembelajaran PPKN Melalui Pengenalan Kearifan Lokal - Andriyani, Yunita; Yayang Furi Furnamasari; Umar Umar (Pusat Riset dan Inovasi Nasional, 2023)
This research was conducted to address the negative impact of globalization that can diminish a sense of patriotism and to improve the quality of Pancasila and Citizenship Education (PPKN) in SDN Pengadilan 2 Bogor by integrating local wisdom. The research aimed to understand how the introduction of local wisdom in PPKN teaching could shape the values of Pancasila in student profiles and help students grow into intelligent and character-driven generations. The research method employed was qualitative with descriptive analysis. Data were collected through interviews, questionnaires, literature review, and documentation. The results revealed six Pancasila student profile values in the implementation of local wisdom introduction at SDN Pengadilan 2 Bogor. Out of the 40 participating students, 3 students (8%) fell into the